Ultraflat graphene - Lui, Chun Hung; Liu, Li; Mak, Kin Fai; Flynn, George W.; Heinz, Tony F. (Nature (London), 2009)
Graphene: new process yields ultraflat form Graphene is the subject of intense research thanks to its novel fundamental properties and its potential for possible electronics applications. Though graphene is essentially two-dimensional, a layer of carbon atoms just one atom thick, it is in fact always slightly crumpled. Whether laying on a substrate or suspended, it always presents ripples, which are thought to define a remarkably diverse set of the observed properties of graphene. Now a team from Columbia University has developed a simple, but effective method of producing ultraflat graphene by deposition on an atomically flat mica surface that tightly binds to the carbon atoms. Thus ripple formation is not an essential feature of high-quality graphene. The availability of ultraflat samples will facilitate studies of the effect of ripples on the physical and electronic properties of graphene. Graphene, an atom-thin carbon sheet is interesting for its fundamental properties as well as for its possible applications in electronics, is not strictly two-dimensional. Microscopic corrugations, or ripples, have been observed in all graphene sheets so far. Direct experimental study of the physics of such ripples has been hindered by the lack of flat graphene layers. Ultraflat graphene is now achieved through its deposition on the atomically flat terraces of cleaved mica surfaces. Graphene, a single atomic layer of carbon connected by sp 2 hybridized bonds, has attracted intense scientific interest since its recent discovery 1 . Much of the research on graphene has been directed towards exploration of its novel electronic properties, but the structural aspects of this model two-dimensional system are also of great interest and importance. In particular, microscopic corrugations have been observed on all suspended 2 and supported 3 , 4 , 5 , 6 , 7 , 8 graphene sheets studied so far. This rippling has been invoked to explain the thermodynamic stability of free-standing graphene sheets 9 . Many distinctive electronic 10 , 11 , 12 and chemical 13 , 14 , 15 properties of graphene have been attributed to the presence of ripples, which are also predicted to give rise to new physical phenomena 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 that would be absent in a planar two-dimensional material. Direct experimental study of such novel ripple physics has, however, been hindered by the lack of flat graphene layers. Here we demonstrate the fabrication of graphene monolayers that are flat down to the atomic level. These samples are produced by deposition on the atomically flat terraces of cleaved mica surfaces. The apparent height variation in the graphene layers observed by high-resolution atomic force microscopy (AFM) is less than 25 picometres, indicating the suppression of any existing intrinsic ripples in graphene. The availability of such ultraflat samples will permit rigorous testing of the impact of ripples on various physical and chemical properties of graphene.